Air Quality Indices Assessment in Artisanal Gold Mining Areas of Zamfara State, Nigeria - Bate, Garba Barde (Indonesian Journal of Applied Environmental Studies, 2023)
Mining processes contribute significantly to air pollution which has been identified as the largest cause of human deaths worldwide. This research was therefore conducted to assess air pollution of three gold mining areas: Kwali,  Maraba, Duke and a non–mining area: Kadauri in Zamfara State, Nigeria. Monthly measurements of CO, SO2 and NO2 wasdone using Gasman detection instrument (Crowcon–EExias IIC T5), particulates were determined using optical counter, buffered KI solution was used to measure O3 while temperature, humidity and pressure were measured using their respective meters over a period of one year. Air quality indices were calculated using the USEPA (1999) AQI formula, pollutants and meteorological factors relationships were determined using Pearson’s correlation and seasonal variation was measured using T–test. Highest and lowest CO were 25.85±7.42 µg/m3 in Kwali and 12.08±3.32 µg/m3 in Kadauri respectively, SO2 was also highest (48.15±12.42 µg/m3) and lowest (31.74±6.67 µg/m3) in Kwali and Kadauri respectively. O3 was highest (151.29±29.74 ppb) and lowest (107.38±21.95 ppb), while PM10 was highest (498.37±48.49 µg/m3) and lowest (319.31±44.86 µg/m3) in Duke and Kadauri respectively. Air quality parameters generally exceeded the WHO limit while CO, SO2, and PM2.5 had significant difference (P0.05) across sampling stations. Mining areas had hazardous AQI with Duke being the highest (392) and Kadauri had 248 implying very unhealthy atmosphere. Pollutants correlated negatively with humidity and positively with pressure, temperature inversely correlated with NO2, SO2 and PM2.5 while pollutants’ dry season concentrations were significantly higher. Information and regulation of mining activities is suggested as well as the use of PPEs.